The influence of people's business credit (KUR) capital from Pt. Bank Rakyat Indonesia, own capital, and business length in supporting msme income in the malioboro region - Fransisco Aldrin Ohoiwirin; Ratri Paramitalaksmi (Indonesia Accounting Research Journal, 2025)
This research seeks to examine the impact of micro, small, and medium companies (MSMEs) in the Malioboro region, Yogyakarta, on their revenue, taking into account their own capital, the influence of People's operation Credit (KUR) from PT. Bank Rakyat Indonesia, and the length of their operation.  A total of 44 micro, small, and medium-sized enterprises (MSME) that have used KUR services were polled using a quantitative methodology.  Several tests for validity, reliability, and classical assumptions were run on the data, in addition to multiple linear regression.  While personal capital significantly and positively impacted income growth, KUR had no discernible influence on MSME income, according to the research.  On the other hand, there was a negative and statistically significant influence of company longevity, suggesting that there has to be constant innovation in company operations.  At the same time, the three independent factors had a 33.2% impact on MSME income.  To maintain the growth of micro, small, and medium-sized enterprises (MSME) in Malioboro, a tourist hotspot, these results emphasize the need of internal capital management and creative techniques.